13
$\begingroup$

What is the sum of a shifted sinc function:

$$g(y) \equiv \sum_{n=-\infty}^\infty \frac{\sin(\pi(n - y))}{\pi(n-y)} \, ?$$

$\endgroup$
17
$\begingroup$

We use the Poisson summation formula. Define $f(x) \equiv \sin(\pi x) / (\pi x)$. Then the sum we are trying to solve is $$g(y) = \sum_{n=-\infty}^\infty f(n-y) \, .$$ The Poisson summation formula converts the sum over values of $f$ to a sum over values of the Fourier transform of $f$.

Poisson summation

Note that $g(y)$ is periodic with period $1$. The Fourier series coefficients of $g$ are by definition \begin{align} g_\nu &= \int_0^1 dy \, g(y)e^{-i 2 \pi \nu y} \\ &= \int_0^1 dy \, \sum_{n=-\infty}^\infty f(n-y) e^{-i 2 \pi \nu y} \\ (\text{Let }x\equiv n-y) \qquad &= \sum_{n=-\infty}^\infty \int_{n-1}^n dx \, f(x) e^{-i 2 \pi \nu (n-x)} \\ &= \int_{-\infty}^\infty dx \, f(x) e ^{i 2 \pi \nu x} \\ &= \tilde{f}(-\nu) \, . \end{align} where $\tilde{f}$ is the Fourier transform of $f$.

By definition of the Fourier series, \begin{align} g(y) &= \sum_{\nu = -\infty}^\infty e^{i 2 \pi \nu y} g_\nu \\ \text{so} \qquad \sum_{n=-\infty}^\infty f(n-y) &= \sum_{\nu=-\infty}^\infty e^{-i 2 \pi \nu y} \tilde{f}(\nu) \end{align} which is the Poisson summation formula

Solution to the problem

Using the Poisson summation formula, we can write $$g(y) = \sum_{n=-\infty}^\infty f(n-y) = \sum_{\nu=-\infty}^\infty \tilde{f}(\nu) e^{-i 2 \pi \nu y} \, .$$ What is $\tilde{f}$? We can easily compute that the Fourier transform of the tophat function $$ T(x) = \left\{ \begin{array}{l} 1, \qquad -1/2 < x <1/2 \\ 0, \qquad \text{otherwise} \end{array} \right. $$ is $\tilde{T}(\nu)=\sin(\pi \nu) / (\pi \nu)$. By duality of the Fourier transform, that means that $\tilde{f}$ is the tophat function $T$. Therefore we have $$g(y) = \sum_{\nu=-\infty}^\infty T(\nu) e^{-i 2 \pi \nu y} = 1 \, .$$ This is a remarkable result: no matter how much you shift your sample points on a sinc function, the sum of those samples is constant.

$\endgroup$
1
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} \mrm{g}\pars{y} & \equiv \sum_{n = -\infty}^{\infty}{\sin\pars{\pi\bracks{n - y}} \over \pi\pars{n - y}} = {\sin\pars{\pi y} \over \pi y} + \sum_{n = 1}^{\infty}\bracks{% {\sin\pars{\pi\bracks{n - y}} \over \pi\pars{n - y}} + {\sin\pars{\pi\bracks{-n - y}} \over \pi\pars{-n - y}}} \\[5mm] & = -\,{\sin\pars{\pi y} \over \pi y} + \sum_{n = 0}^{\infty}\bracks{% {\sin\pars{\pi\bracks{n - y}} \over \pi\pars{n - y}} + {\sin\pars{\pi\bracks{n + y}} \over \pi\pars{n + y}}} \end{align}

Note that

$\ds{\bracks{{\sin\pars{\pi\bracks{z - y}} \over \pi\pars{z - y}} + {\sin\pars{\pi\bracks{z + y}} \over \pi\pars{z + y}}} \expo{-2\pi\,\verts{\Im\pars{z}}} \stackrel{\mrm{as}\ \Im\pars{z}\ \to\ \pm\infty}{\large\sim} \pm{\expo{-\pi\verts{\Im\pars{z}}} \over \pi\,\Im\pars{z}} \stackrel{\mrm{as}\ \Im\pars{z}\ \to\ \pm\infty}{\large\to}{\large 0}}$

such that the sum can be evaluated by means of the Abel-Plana Formula: \begin{align} \mrm{g}\pars{y} & = -\,{\sin\pars{\pi y} \over \pi y} + \int_{0}^{\infty}\bracks{% {\sin\pars{\pi\bracks{x - y}} \over \pi\pars{x - y}} + {\sin\pars{\pi\bracks{x + y}} \over \pi\pars{x + y}}}\dd x \\[2mm] & + {1 \over 2} \bracks{{\sin\pars{\pi\bracks{x - y}} \over \pi\pars{x - y}} + {\sin\pars{\pi\bracks{x + y}} \over \pi\pars{x + y}}}_{\ x\ =\ 0} \\[5mm] & = -\,{\sin\pars{\pi y} \over \pi y} + {1 \over 2}\int_{-\infty}^{\infty}\bracks{% {\sin\pars{\pi\bracks{x - y}} \over \pi\pars{x - y}} + {\sin\pars{\pi\bracks{x + y}} \over \pi\pars{x + y}}}\dd x \\[2mm] & + {\sin\pars{\pi y} \over \pi y} = {1 \over 2}\int_{-\infty}^{\infty}{\sin\pars{\pi x} \over \pi x}\,\dd x + {1 \over 2}\int_{-\infty}^{\infty}{\sin\pars{\pi x} \over \pi x}\,\dd x = \bbx{\Large 1} \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.